PROBLEMATIKA IMPLEMENTASI METODE EVERYONE IS A TEACHER HERE PADA PEMBELAJARAN PAI DI SMK NEGERI 1 BANYUDONO - Kolistiani, Nur Antika; Inayati, Nurul Latifatul (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
The change from the 2013 curriculum to an independent curriculum presents new problems for teachers in learning activities. This research aims to find out what problems occur in implementing the Everyone Is A Teacher Here method at SMK Negeri 1 Banyudono and what solutions can be made. This type of research uses descriptive qualitative research with data sources namely Islamic Religious Education teachers and students of class students themselves and are embarrassed to express their opinion, the teacher as a facilitator does not work well, and learning time is limited. The solution to overcome this problem is: the teacher must be able to increase students' interest and motivation in learning, allow students to search for answers in books or the internet, the teacher provides reading references other than the module and divides the class into two groups.